Automated extension of existing material flow simulations by energy aspects Automatisierte Erweiterung bestehender Materialfluss-simulationen durch Energieaspekte - Spreng, Simon; Kohl, Johannes; Franke, Jörg (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2013)
Due to the growing social consciousness, the production factor energy becomes not only expensive, but also highly influences the company's image. In order to realize the resulting production requirements, simulation tools appear to be reasonable, since they are capable of revealing energy consumptions without stopping the production process.
CRIS-Team Scopus Importer:2023-03-07